Community Pharmacists Knowledge, Behaviours and Practice of Adverse Drug Reactions Reporting in Lagos State, Nigeria. - Usifoh, Stella Folajole; Aika, Isabel Naomi; Odili, Valentine Uche; Nwokoro, Jerome Onyisi (Indian Journal of Pharmacy Practice)
Introduction: Adverse Drug Reaction (ADR) reporting is essential to ensure safe use of medication. Objective: To assess community pharmacists’ knowledge, behaviours and practice of ADR reporting in Lagos State. Methods: This was a cross-sectional survey using self-administered questionnaire distributed to randomly selected pharmacists in retail community pharmacies in Lagos State. The instrument is a 62 item structured questionnaire in four sections; the demographics, knowledge about ADR reporting system, assessment of practice and attitude on ADR reporting; and the behavior and practice of patients counseling about ADR by community pharmacists. Data analysis was done with Statistical Package for the Social Sciences (SPSS) version 20. Results: Majority (31.9%) of the respondents have practiced in community pharmacies for less than 5 years, 62.7% of the community pharmacists were familiar with adverse drug reaction reporting. 57.8% of the pharmacists have internet facility in their pharmacies and 79.4% of the respondents were aware that community pharmacists can submit adverse drug reactions online. In the preceding months, 78.4% of the pharmacists had encountered many serious ADR but only 27.0% reported them. The reasons for underreporting of ADR included uncertainty about causality (52.0%), respondents not sure of which ADR to report (38.2%), no access to reporting forms (33.8%), ignorance of the rule of reporting (30.4%), and complexity of the reporting forms (16.2%). Conclusion: There is low reporting of adverse drug reactions by community pharmacists attributable to insufficient knowledge and high level of untrained community pharmacists in pharmacovigilance and adverse drug reactions reporting.
Keywords: Adverse drug reaction (ADR); Community pharmacists; Pharmacovigilance; Reporting.